Role of voltage-gated chloride channels in epilepsy: current insights and future directions - Ni, Ming-Ming; Sun, Jie-Yu; Li, Zheng-Qian; Qiu, Jin-Chun; Wu, Chun-Feng (Frontiers in Pharmacology, 2025)
Epilepsy is a prevalent chronic neurological disorder characterised by recurrent seizures caused by excessive neuronal discharge. Disruptions in chloride ion homeostasis significantly affect neuronal excitability, and play a crucial role in the pathophysiology of this disorder. This review highlights the emerging importance of chloride voltage-gated channels in epilepsy, which has been largely underappreciated compared to cation channels. Recent studies have suggested that genetic alterations in chloride channels, such as CLCN1, CLCN2, CLCN3, CLCN4, and CLCN6, contribute to neuronal excitability and seizure susceptibility, with variations in these channels acting more as susceptibility factors than direct causes. However, there is a significant gap in the research on other chloride channels, particularly ClC-Ka, ClC-Kb, ClC-5, and ClC-7, whose roles in epilepsy remain underexplored. Future research should focus on these channels to better understand their contribution to the pathophysiology of epilepsy. The incorporation of genetic tests for chloride channel variants in clinical practice could provide valuable insight into the aetiology of epilepsy, leading to improved diagnostic and therapeutic strategies for affected individuals.